Trend Point 11 of the SDGs: The Potential of the Giri Kedaton Site in Discussing Eco-Spiritualism Philosophy - Rahmatta Thoriq Lintangesukmanjaya; Ilmiawan Hakim; Nabila Nur Almaida Nasution; Binar Kurnia Prahani; Dwikoranto Dwikoranto; Khoirun Nisa’ (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: Identifying global aspects of eco-spiritualism and analyzing its potential at the Giri Kedaton site to achieve SDG 11, which aims to create inclusive and sustainable settlements. Method: The research was conducted using a mixed-methods research model. This research approach combines qualitative methods (Bibliometric Analysis) and quantitative methods (Observation) in one study to gain a more comprehensive understanding of a phenomenon. Results: There is a global research trend in philosophy supporting the SDGs. The number of documents and citations increased from 2020 to 2025, resulting in 48 Scopus documents, with the highest number of citations in 2024 at 185. Bibliometric analysis findings identified three main aspects of eco-spiritualism: philosophical foundations, environmental ethics, and integration practices. The Giri Kedaton site, as a cultural heritage site, has the potential to uphold the values ​​of eco-spiritualism and SDG 11 for global recognition. Novelty: The environmentally friendly principles of sustainable settlement management, in accordance with SDG 11, are reflected in the Giri Kedaton site. The potential for comfortable living and inclusive settlements is a key aspect of SDG 11. Analysis of the findings opens up new insights into the realm of eco-spirituality related to the beliefs and philosophy of the Giri Kedaton site.